Mitochondrial Dynamics in Cardiovascular Medicine - Santulli, Gaetano (Springer International Publishing Imprint: Springer, 2017)
This text covers the basic principles of mitochondrial dynamics in cardiovascular medicine, with particular emphasis on their functional roles in physiology and disease. The book will include articles pertaining to mitochondrial fitness on a global basis, providing therefore an update on the progress made in several aspects in the field. Thus, it will assist scientists and clinicians alike in furthering basic and translational research. Organized in sections focusing on: basic science, mitochondrial dysfunction in cardiac disorders, in vascular disorders, in metabolic disorders, in kidney disease, therapeutic challenges and options, this essential volume fills imperative gaps in understanding and potentially treating several cardiovascular disorders